A composite device for viscosupplementation treatment resistant to degradation by reactive oxygen species and hyaluronidase - Toropitsyn, Evgeniy; Pravda, Martin; Rebenda, David; Ščigalková, Ivana; Vrbka, Martin; Velebný, Vladimír (Journal of biomedical materials research. Part B, Applied biomaterials, 2022)
Osteoarthritis (OA) is one of the most common musculoskeletal disorders in the world. OA is often associated with the loss of viscoelastic and tribological properties of synovial fluid (SF) due to degradation of hyaluronic acid (HA) by reactive oxygen species (ROS) and hyaluronidases. Viscosupplementation is one of the ways how to effectively restore SF functions. However, current viscosupplementation products provide only temporal therapeutic effect because of short biological half-life. In this article we describe a novel device for viscosupplementation (NV) based on the cross-linked tyramine derivative of HA, chondroitin sulfate (CS), and high molecular weight HA by online determination of viscoelastic properties loss during degradation by ROS and hyaluronidase. Rheological and tribological properties of developed viscosupplement were compared with HA solutions with different molecular weights in the range 500-2000 kDa, which are currently commonly used as medical devices for viscosupplementation treatment. Moreover, based on clinical practice and scientific literature all samples were also diluted by model OA SF in the ratio 1:1 (vol/vol) to better predict final properties after injection to the joint. The observed results confirmed that NV exhibits appropriate rheological properties (viscosity, elastic, and viscous moduli) comparable with healthy SF and maintain them during degradation for a significantly longer time than HA solutions with molecular weight in the range 500-2000 kDa and cross-linked material without CS.
Keywords: viskosuplementace; Viscosupplementation; lidé; artróza kolenních kloubů; tyramin; Tyramine; viskosuplementy; Injections, Intra-Articular; osteoartróza; reaktivní formy kyslíku; Osteoarthritis, Knee; chondroitinsulfáty; Hyaluronoglucosaminidase; Chondroitin Sulfates; kyselina hyaluronová; Hyaluronic Acid; injekce intraartikulární; hyaluronoglukosaminidasa; Reactive Oxygen Species; Humans; Osteoarthritis; Viscosupplements